The Effect of Chronic Alcohol Intoxication on the Daily Rhythm of Some Micromorphometric Parameters of Rat Hepatocytes - Kirillov, Y.A.; Kozlova, M.A.; Makartseva, L.A.; Areshidze, D.A.; Kucher, S.A.; Chernov, I.A.; Shtemplevskaya, E.V. (Journal of Pharmacy and Nutrition Sciences, 2021)
The effect of chronic alcohol intoxication on the daily rhythm of micromorphometric parameters characterizing the morphological and functional state of the liver is studied on 80 male Wistar rats of 6 months age, divided into 2 equal groups. The first group served as control; rats of the second group (experiment) were kept under similar conditions but got as a drink a 15% ethanol solution ad libitum instead of water. After three weeks of the experiment, animals were euthanized consistently at four-time points during the day. The pathomorphological study of the liver was carried out, the daily dynamics of the nucleus and cell (by area and nuclear-cytoplasmic ratio (NCR)), ploidy of mononuclear hepatocytes, and the proportion of binuclear hepatocytes were measured. The reliability of circadian rhythm (CR) was determined by cosinor analysis. The study indicates complex changes in the organization of rhythmostasis in the experiment. The chrono-destructive effect of experimental alcohol intoxication on the CR of the cell and NCR, as well as the chronomodulating effect to the CR of the nucleus are established. The effect of ethanol on the CR of ploidy and the number of binuclear hepatocytes, as well as on the nature of their variation at the studied time points is established. An increase in the ploidy of hepatocytes and an in the number of binuclear cells is revealed, which indicates the beginning of the deployment of adaptive-compensatory reactions in the organ.